A bond-free PPLN thin film ridge waveguide. (July 2023) - Feng, Xinkai; Chen, Huaixi; Huang, Haizhou; Zhang, Xinbin; Cheng, Xing; Chen, Jiaying; Ma, Lei; Liu, Huagang; Liang, Wanguo; Lin, Wenxiong
Highlights: A novel fabrication method of PPLN thin film ridge waveguide. This method does not need wafer-wafer bonding, ion implantation and long-time annealing. PPLN thin film ridge waveguide with a trapezoidal substrate was fabricated using the new method. SHG bandwidth spreading is possible with trapezoidal substrate PPLN thin film ridge waveguides. Abstract: Lithium niobate thin film waveguide is attractive in nonlinear frequency conversion, especially in the second harmonic generation (SHG). However, the conventional fabrication method of lithium niobate thin film waveguide requires expensive bonding equipment and the prepared film is easy to peel off. In this paper, a novel fabrication method of PPLN thin film ridge waveguide with a trapezoidal substrate is presented, based on glue bonding. The PPLN waveguide together with its trapezoidal substrate is surrounded with low refractive glue to modulate the vertical refractive index gradient along the waveguide length, which was proved to be useful for broadband SHG with a theoretical bandwidth above 25 nm by changing the substrate thickness from 3 μm to 17 μm. The proposed structure was verified by using a C-band ASE laser as the pump source, where the SHG laser bandwidth is about 11 nm. The power of SHG is 2.55 μw, and the normalized conversion efficiency is 10.5 %/W∙cm 2 . This work is beneficial to simplify the fabrication process of lithium niobate thin film ridge waveguide, and has certain promotion significance for photonic chip integration.